Herbicidal and Plant-growth Stimulating Effects of Phenolic Compounds Isolated from Lichens - Marize Terezinha L. Pereira Peres; Ana M. Mapeli; Odival Faccenda; Neli Kika Honda (Orbital: The Electronic Journal of Chemistry, 2015)
The depsides atranorin (7) and diffractaic acid (1), the depsidones hypostictic (2) protocetraric (3), salazinic (4) acids, the xanthone secalonic acid (5), and usnic acid (6) were evaluated for their phytotoxic potentials against the target species Allium cepa cv. Baia periforme (onion, Monocotyledoneae). The bioassays, carried out under laboratory conditions, revealed that diffractaic (1) and hypostictic (2) acids stimulated plant growth; secalonic acid (5) stimulated seed germination and radicle growth, while reducing coleoptile length. Usnic acid (6) promoted seed germination and stronger inhibition of radicle and coleoptile growth. Protocetraric (3) and salazinic (4) acids and atranorin (7) exhibited a herbicidal effect, inhibiting seed germination and reducing radicle and coleoptile growth—features that suggest their utility as natural herbicides. These results invite further investigation to elucidate the mode of action of these compounds and to synthesize them for field experiments.DOI: http://dx.doi.org/10.17807/orbital.v7i3.756